Runaway electron generation and control. (16th November 2016) - Esposito, B; Boncagni, L; Buratti, P; Carnevale, D; Causa, F; Gospodarczyk, M; Martin-Solis, JR; Popovic, Z; Agostini, M; Apruzzese, G; Bin, W; Cianfarani, C; et al.
Abstract: We present an overview of FTU experiments on runaway electron (RE) generation and control carried out through a comprehensive set of real-time (RT) diagnostics/control systems and newly installed RE diagnostics. An RE imaging spectrometer system detects visible and infrared synchrotron radiation. A Cherenkov probe measures RE escaping the plasma. A gamma camera provides hard x-ray radial profiles from RE bremsstrahlung interactions in the plasma. Experiments on the onset and suppression of RE show that the threshold electric field for RE generation is larger than that expected according to a purely collisional theory, but consistent with an increase due to synchrotron radiation losses. This might imply a lower density to be targeted with massive gas injection for RE suppression in ITER. Experiments on active control of disruption-generated RE have been performed through feedback on poloidal coils by implementing an RT boundary-reconstruction algorithm evaluated on magnetic moments. The results indicate that the slow plasma current ramp-down and the simultaneous reduction of the reference plasma external radius are beneficial in dissipating the RE beam energy and population, leading to reduced RE interactions with plasma facing components. RE active control is therefore suggested as a possible alternative or complementary technique to massive gas injection.